Plasma CircCYP24A1 as a Novel Biomarker of Esophageal Squamous Cell Carcinoma - Ruolan Zhang M.M.; Jianlin Liu M.M.; Hang Yang M.M.; Jinsong Tan M.M.; Rong Xiong M.M.; Yun Liu MM; Gang Feng PhD; Guiqin Song PhD; Kang Liu PhD (Technology in Cancer Research & Treatment)
Background A clinical challenge in esophageal squamous cell carcinoma (ESCC) remains the lack of applicable plasma biomarkers for screening and diagnosis. Circular RNAs (circRNAs) hold great potential as biomarkers for cancer. The study aims to explore a circRNA as a potential plasma biomarker for screening strategies and diagnostic approaches to ESCC. Methods Upregulated circRNAs were identified through RNA sequencing, with circCYP24A1 being identified as the target circRNA. Fluorescence in situ hybridization was employed to detect the expression of circCYP24A1 in ESCC tissue microarrays, aiming to assess the expression of circCYP24A1 in a large population and its correlation with clinical indicators. Subsequently, qRT-PCR analysis was performed on plasma samples from both ESCC patients and healthy controls to evaluate the expression levels of circCYP24A1, exploring its potential as a biomarker. Finally, the functions of circCYP24A1 were validated through CCK-8 assay, wound healing assay, trans-well assays and western blot assays. Results CircCYP24A1 demonstrated upregulation in both plasma and tissues, exhibiting correlations with lymph node metastasis, TNM staging, and prognosis in ESCC. The circCYP24A1 achieved a perfect area under the curve of 0.94 for the diagnosis of ESCC, and an area under the curve of 0.76 for the prediction of lymph node metastasis. Furthermore, functional loss assays revealed that circCYP24A1 effectively promotes the epithelial-mesenchymal transition and tumor metastasis in vitro. Conclusions CircCYP24A1 emerges as a potential plasma diagnostic biomarker and a predictive factor for LNM for ESCC.